Fees for Providing Information in the Age of Digitalization - Janderová, Jana (Walter de Gruyter GmbH & Co. KG, 2024)
The article examines the principle of transparency as a cornerstone of the rule of law and a deterrent to power misuse. Effective and efficient means must be used to ensure access to government information. However, under EU and Czech law, persons legally bound to provide information are entitled to request reimbursements of their costs. Such fees may be requested in an amount specified by law, namely for excessive information search which usually form the most significant part of the fees charged. Contrarily, the Troms & oslash; Convention does not allow for reimbursement of extensive search. This article investigates whether these fees impede access to information. The Czech Supreme Administrative Court's and Constitutional Court's case law defining the conditions under which reimbursement of costs may be requested is analysed. Further, current administrative practice of ministries and regional authorities is compared, highlighting considerable disparities in their fee schedules. The article scrutinizes the amount of fees collected, which is rather insignificant and posits that the principle of effectiveness, which initially justified these charges, has been superseded in the digital age. The research, which has both national and EU-wide implications, concludes that it would be beneficial to abolish all fees. This recommendation also applies to other countries with a similar approach to information access. The findings of this research offer valuable insights for both the scientific community and practical applications in the field of law.
Úhrada za poskytování informací v době digitalizace
Keywords: access to information; digitalization; fees; transparency; Tromso Convention; přístup k informacím; digitalizace; úhrada; transparentnost; Tromsøská úmluva